KOMPETENSI PERAWAT DAN PATIENT SAFETY DI RSUD PIRU KABUPATEN SERAM BAGIAN BARAT - Irhamdi Achmad (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2018)
Patient safety in hospitals is a global issue and it is important to establish a safer and more comfortablesystem of nursing and health services in hospitals. Nursing care is expected to be of good quality anduseful in preventing incidents of unwanted events that can harm patients and hospitals. The reality inthe hospital even though the socialization and training of patient safety have been carried out by thehospital to nurses and health workers there are still cases of injured patients, patients falling and wrongtreatment. This study aims to determine the relationship of nurse competencies that was nursingstudies, nursing ethics, drug administration and measurement of vital signs with patient safety in PiruHospital in 2017. The type of research is descriptive analytic with design cross-sectional. Theinstrument used was a questionnaire, with a sample of 66 nurses at the Piru Hospital in Seram BagianBarat District. The results showed that there was a relationship between significant nursing assessmentcompetencies, nursing ethics, administration of drugs and the measurement of vital signs with patientsafety, at the Piru Hospital. Therefore nurses' knowledge and technical skills regarding patient safetythrough various socialization and training activities must be improved so that the safety and security ofpatients in hospital services is guaranteed and the hospital image becomes better. Keywords: Nurse competence, patient safety, hospital